Penile cancerina 23-Year-old associated with HPV 62 infection– Case report - Carvalho, Julio José M; Moreira, Raphael de Jesus; Vedovato, Bruno Cesar; Silva, Dalmo B; Carvalho, Julio ZM; Trevizol, Alisson Paulino; Simabukuro, Artur M (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: cancer of the penis is a rare malignant disease, causing high morbidity and mortality, which mostly affects elderly men. It has a peak incidence in the seventh decade of life, very rare in young people. In some countries in Africa, Asia and South America represents about 10% of the malignancies that affect men. In Brazil, penile cancer represents 2% of all cancers in men and is most common in the north and northeast of the country, where the incidence rate varies from 1.3 to 2.7 per 100.000. Poor penile hygiene, smegma retention, and phimosis are considered risk factors for penile cancer. In populations that practice circumcision, the incidence of penile cancer is low, even in underdeveloped countries like Nigeria and India. There are many studies in the literature pointing HPV infection as the probable cause, with the probable initial precursor the initial verrucosa. Case report: patient E.G.S., male, 23 years, white, catholic, without studying, working with telephony, native from Osasco (SP), born in Barueri (SP). He is married and has no children. The patient reports that he had had phimosis since childhood, which precluded complete exposure of the glans. In November 2010 reported the appearance of a nodule with 1 cm in diameter in the penis. Circumcision was performed on February 24, 2011 for the treatment of phimosis, and a biopsy was performed during the treatment, diagnosed as squamous cell carcinoma grade III. Biomolecular study showed HPV 62 infection. Partial penectomy was performed to remove the injury on 21/03/2011. At surgery, the injury already had with 7 x 5 x 4 cm, ulcerative-infiltrative lesion of 3 x 5 cm, 1 cm away from the urethral orifice. Discussion: our patient had phimosis which precluded complete exposure of the glans in childhood, affecting penile hygiene. Phimosis predisposes to squamous cell and urine and waste (smegma) retention, that can cause chronic irritation with or without bacterial infection of the glans or foreskin. Circumcision decreases the chance of contracting sexually transmitted diseases, urinary tract infections and provides better hygiene. It is also associated with lower incidence of HPV, which shows itself as an important risk factor for the development of penile cancer. There was dramatic reduction in the persistence of the virus among circumcised patients, up to 90%, being important in the resolution of infection and protection against malignancy. The HPV 62 was found in female patients, causing squamous intraepithelial lesions of high degree, compatible with lesions of more oncogenic subtypes of HPV.